Capturing readiness to learn and collaboration as explored with an interprofessional simulation scenario: A mixed-methods research study. (January 2016) - Rossler, Kelly L.; Kimble, Laura P.
Summary: Background: Didactic lecture does not lend itself to teaching interprofessional collaboration. High-fidelity human patient simulation with a focus on clinical situations/scenarios is highly conducive to interprofessional education. Consequently, a need for research supporting the incorporation of interprofessional education with high-fidelity patient simulation based technology exists. Objectives: The purpose of this study was to explore readiness for interprofessional learning and collaboration among pre-licensure health professions students participating in an interprofessional education human patient simulation experience. Methods: Using a mixed methods convergent parallel design, a sample of 53 pre-licensure health professions students enrolled in nursing, respiratory therapy, health administration, and physical therapy programs within a college of health professions participated in high-fidelity human patient simulation experiences. Perceptions of interprofessional learning and collaboration were measured with the revised Readiness for Interprofessional Learning Scale (RIPLS) and the Health Professional Collaboration Scale (HPCS). Focus groups were conducted during the simulation post-briefing to obtain qualitative data. Statistical analysis included non-parametric, inferential statistics. Qualitative data were analyzed using a phenomenological approach. Results: Pre- and post-RIPLS demonstrated pre-licensure health professions students reported significantly more positive attitudes about readiness for interprofessional learning post-simulation in the areas of team work and collaboration, negative professional identity, and positive professional identity. Post-simulation HPCS revealed pre-licensure nursing and health administration groups reported greater health collaboration during simulation than physical therapy students. Qualitative analysis yielded three themes: "exposure to experiential learning, " "acquisition of interactional relationships, " and "presence of chronology in role preparation." Quantitative and qualitative data converged around the finding that physical therapy students had less positive perceptions of the experience because they viewed physical therapy practice as occurring one-on-one rather than in groups. Conclusion: Findings support that pre-licensure students are ready to engage in interprofessional education through exposure to an experiential format such as high-fidelity human patient simulation. Highlights: Readiness for interprofessional learning with simulation was explored. Significantly more positive attitudes in readiness to learn were demonstrated. Perceptions of collaboration were different among health profession student groups. Students reported the simulation-enhanced interprofessional communication. Students are ready to engage in interprofessional education with simulation.